New Media Egologies - Martín Prada, Juan (Re-visiones, 2024)
This article addresses the notion of the web as a mirrored sphere. The debate about the primacy of a psychomorphic vision of reality, associated with the use of the new technologies of connectivity, is here related with the practices of self-representation and hipervisibilisation that are characteristic of the new communicative and social habits that take place in the network-system.